Distribution of Rifampicin-Resistant Tuberculosis Patients based on Presumptive Drug-Resistant Tuberculosis Criteria at Dr. Hasan Sadikin Hospital 2016–2019 - Dinda Nursyafira Misyatin; Arto Yuwono Soeroto; Ferdy Ferdian (Althea Medical Journal, 2022)
Background: Diagnosis of drug-resistant tuberculosis (DR-TB) begins with identifying presumptive DR-TB patients using Xpert MTB/RIF, as a diagnostic test to detect resistance to rifampicin. The study aimed to identify the distribution of rifampicin-resistant tuberculosis (RR-TB) patients based on presumptive DR-TB criteria at Dr. Hasan Sadikin General Hospital Bandung. Moreover, this study also explored the Xpert MTB/RIF Ct values.Methods: This was a descriptive-retrospective study from 570 medical records of DR-TB patients collected at the Multidrug-resistant tuberculosis (MDR-TB) clinic of Dr. Hasan Sadikin General Hospital from 2016 to 2019. The inclusion criteria were suspected patients with the Xpert MTB/RIF Ct values in the very low-low and medium-high categories. Data were analyzed using frequency distribution. Results: The most common presumptive DR-TB criteria among DR-TB patients were relapse cases (52.3%). Presumptive DR-TB criteria, with a high percentage result of medium-high Ct values, were category II treatment failure (80.9%).Conclusion: Relapse case and category II treatment failure are presumptive DR-TB criteria, which need more attention from clinicians.